A systematic review of the patient reported outcome measures used to assess the impact of periodontitis and peri-implantitis on oral health related quality of life - Joshua M. Jackson; Richard Holliday; James S. Hyde; Helen J. Rogers (BDJ Open)
Abstract Introduction Periodontal disease (PD) and peri-implantitis (PI) can have a significant impact on oral health related quality of life. It is important that any patient reported outcome measures accurately reflect this impact. Aims To identify the measures used to assess the impact of periodontal disease and peri-implantitis on oral health related quality of life. To assess the psychometric properties of the measures identified by applying an adapted version of the Consensus-based standards for the selection of health measurement instruments (COSMIN) checklist. Materials and methods A search of the literature incorporated relevant MeSH terms across four separate databases: Scopus, Web of Science, Medline and Embase. Following the removal of duplicates, studies meeting the inclusion criteria were screened. Any condition specific measure or a measure appearing greater than five times was analysed in accordance with the COSMIN criteria. Results A total of 2103 articles were identified, of which 140 proceeded to full text review. A total of eight different OHRQoL measures were identified and psychometrically analysed. Discussion The majority of measures used to assess the impact of PD and PI were not validated on local populations and were non-specific, generated by clinicians and researchers. The three condition specific measures were adaptations of the Oral Health Impact Profile, a non-specific patient reported outcome measure which may not accurately reflect the specific signs, symptoms and overall impact of PD/PI on an individual’s OHRQoL. Conclusion There is a necessity for a condition-specific instrument to be developed to ensure that the impact of periodontal disease and peri-implantitis on OHRQoL is captured accurately.